Scalar quantum electrodynamics via Duffin-Kemmer-Petiau gauge theory in the Heisenberg picture: Vacuum polarization - Beltran, J. [UNESP]; Maia, N. T. [UNESP]; Pimentel, B. M. [UNESP] (World Scientific Publishing, 2018)
Scalar Quantum Electrodynamics is investigated in the Heisenberg picture via the Duffin-Kemmer-Petiau gauge theory. On this framework, a perturbative method is used to compute the vacuum polarization tensor and its corresponding induced current for the case of a charged scalar field in the presence of an external electromagnetic field. Charge renormalization is brought into discussion for the interpretation of the results for the vacuum polarization.
Keywords: Duffin-Kemmer-Petiau equation; Gunnar Källén; Heisenberg picture; Scalar quantum electrodynamics; vacuum polarization